Decision-making tools for urban regeneration processes: from Stakeholders Analysis to Stated Preference Methods - Bottero, Marta; Mondini, Giulio; Datola, Giulia (TeMA - Journal of Land Use, Mobility and Environment, 2017)
Urban regeneration operations are connected to the creation of a multiplicity of benefits, both economic and extra-economic, that range from the increase in the environmental quality to the amelioration of the urban image, from the valorization of the cultural heritage to the creation of economic development processes. The articles aims at proposing an integrated evaluation approach for addressing decision problems in the context of urban regeneration operations. Starting from the real case of the regeneration programme of the city of Collegno (Italy), the contribution proposes an original evaluation model based on the combined use of Stakeholders Analysis and Stated Preference Methods. The results of the research shows the people’s perception about the social value of urban regeneration programme and their Willingness To Pay for specific transformation operations.